Agile Processes in Software Engineering and Extreme Programming 23rd International Conference on Agile Software Development, XP 2022, Copenhagen, Denmark, June 13-17, 2022, Proceedings - Stray, Viktoria; Stol, Klaas-Jan; Paasivaara, Maria; Kruchten, Philippe (Lecture Notes in Business Information Processing, 2022)
This open access book constitutes the proceedings of the 23rd International Conference on Agile Software Development, XP 2022, which was held in Copenhagen, Denmark, in June 2022. XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends.  XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. This year's conference was held with the theme "Agile in the Era of Hybrid Work". The 13 full papers and 1 short paper presented in this volume were carefully reviewed and selected from 40 submissions. They were organized in topical sections named: agile practices; agile processes; and agile in the large.